Effect Of Work Experience And Work Environment On Employee Satisfaction In The Nusantara Estate 7 Sector Vii Kedaton - Viola De Yusa; Besti Lilyana; Lamtiurmaida Lubis (University of Sang Bumi Ruwa Jurai, 2017)
A success of companies is strongly affected by employee job satisfaction. Every company always attempts to improve employee satisfaction so that it is expected that the companies goals are achieved. Several factors improving the job satisfaction are the work experience and work environment. The objective of this research was partially or simultaneously to determine the effect of the work experience and work environment to employee job satisfaction in the Nusantara State 7 sector VII Kedaton. Type of this research was a quantitative research with the associative method. Setting of this research was in the Nusantara State 7 sector VII Kedaton. The sampling technique used in this research was non-probability random sampling using the disproportional stratified random sampling. The respondents of this research was 57 employees. Data analysis technique used in this research was a multiple linear regression. The hypothesis test used in this research was t-test and f-test. The result of this research showed that (1) the work experience affected the job satisfaction, (2) the work environment affected job satisfaction and work experience, and (3) the work environment affected employee job satisfaction.